2018
DOI: 10.1038/s41598-018-19766-4
|View full text |Cite
|
Sign up to set email alerts
|

The membrane tethered transcription factor EcbZIP17 from finger millet promotes plant growth and enhances tolerance to abiotic stresses

Abstract: The occurrence of various stresses, as the outcome of global climate change, results in the yield losses of crop plants. Prospecting of genes in stress tolerant plant species may help to protect and improve their agronomic performance. Finger millet (Eleusine coracana L.) is a valuable source of superior genes and alleles for stress tolerance. In this study, we isolated a novel endoplasmic reticulum (ER) membrane tethered bZIP transcription factor from finger millet, EcbZIP17. Transgenic tobacco plants overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…Moreover, transgenic rice plants overexpressing OsbZIP66 had enhanced drought tolerance, which was positively correlated with the expression level of OsbZIP66 . In another study, overexpression of the EcbZIP17 gene from finger millet in transgenic tobacco plants conferred enhanced tolerance to abiotic stresses and improved plant growth and yield [120].…”
Section: Bzip Tfsmentioning
confidence: 99%
“…Moreover, transgenic rice plants overexpressing OsbZIP66 had enhanced drought tolerance, which was positively correlated with the expression level of OsbZIP66 . In another study, overexpression of the EcbZIP17 gene from finger millet in transgenic tobacco plants conferred enhanced tolerance to abiotic stresses and improved plant growth and yield [120].…”
Section: Bzip Tfsmentioning
confidence: 99%
“…Ramakrishna et al (2018) showed that overexpression of a finger millet bZIP TF gene EcbZIP17 in tobacco plants resulted in higher germination rate, increased biomass, and increased survival rate in the transgenic plants. Furthermore, the transgenic tobacco plants also showed increased seed yields compared to the control plants.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a chickpea (Cicer arietinum) stress associated TF, CarNAC4 was linked with reduced MDA content and water stress rates in response to salinity and drought stress respectively (Yu et al, 2016). Ramakrishna et al (2018) showed that overexpression of a finger millet bZIP TF gene EcbZIP17 in tobacco plants resulted in higher germination rate, increased biomass, and increased survival rate in the transgenic plants. Furthermore, the transgenic tobacco plants also showed increased seed yields compared to the control plants.…”
Section: Functions Of Transcription Factorsmentioning
confidence: 99%